2015
DOI: 10.1371/journal.pone.0145787
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicine in Children with Cancer: A Study at a Swiss University Hospital

Abstract: BackgroundThough complementary and alternative medicine (CAM) are frequently used by children and adolescents with cancer, there is little information on how and why they use it. This study examined prevalence and methods of CAM, the therapists who applied it, reasons for and against using CAM and its perceived effectiveness. Parent-perceived communication was also evaluated. Parents were asked if medical staff provided information on CAM to patients, if parents reported use of CAM to physicians, and what atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 22 publications
(45 reference statements)
4
49
1
7
Order By: Relevance
“…The current study shows that 23% of the studied cancer patients received Complementary Medicine (CM), this figure is remarkably lower compared to previously reported figures from other countries like Korea (78.5%), Scotland (55%) and Switzerland (53%) [10]. On the other hand, similar finding was reported in Saudi Arabia, where 21.6% of the patients reported receiving CM [9].…”
Section: Discussionsupporting
confidence: 62%
“…The current study shows that 23% of the studied cancer patients received Complementary Medicine (CM), this figure is remarkably lower compared to previously reported figures from other countries like Korea (78.5%), Scotland (55%) and Switzerland (53%) [10]. On the other hand, similar finding was reported in Saudi Arabia, where 21.6% of the patients reported receiving CM [9].…”
Section: Discussionsupporting
confidence: 62%
“…In the literature, several studies have shown that CIH is used in 6–100% of children with cancer (Diorio et al, ; Gottschling et al, ; Magi et al, ). Similar to in the rest of the world, the use of CIH is quite common in Turkey and is reported as being used in between 33.7% and 97.7% of cases (Kurtuncu et al, ; Top et al, ; Turhan & Bör, ).…”
Section: Discussionmentioning
confidence: 99%
“…CIH use is associated with higher parental education levels (Gottschling et al, ; Italia et al, ) and incomes (Gottschling et al, ), and parents take advice from persons with related disease (Gottschling et al, ), friends/neighbors/other mothers (Top et al, ). Parents who thought that the CIH methods they were using were effective (Magi et al, ) would recommend CIH to others (Gottschling et al, ; Magi et al, ), but parents have used CIH methods without informing healthcare providers (Can et al, ; Kurtuncu et al, ; Magi et al, ; Turhan & Bör, ). The use of CIH may interfere with medical treatment, alter the effectiveness of medications, cause adverse effects, and affect compliance with treatment.…”
Section: What Does This Article Add?mentioning
confidence: 99%
“…AM covers a broad and diverse group of treatments and products such as local herbal medicine and botanicals, meditation, specialized diets, vitamins, homeopathy, massage, acupuncture, tai chi, and hypnosis, all of which do not tend to be widely use by conventional health care professionals [15-18]. Not only is AM not widely used by modern health care professionals, there are studies which indicate that it can even have a negative impact when used in conjunction with modern treatments [19].…”
Section: Discussionmentioning
confidence: 99%